Mútuo bancário e vulnerabilidade do consumidor idoso analfabeto - Ribeiro, Ana Cecília Rosário (2016)
Private autonomy in payroll loan contracts is restricted to the applicant decide whether to be subjected to conditions imposed by the pre-written contractual clauses set forth by financial institutions. In order to resolve whether to enter into a contract it is necessary that the individual understands its provisions. No sooner, will one realize difficulties that may be faced by the elderly and illiterate consumer, who do not have the means to know and understand, by himself, the contents of the financial contract. Consumerism law requires, from the supplier, loyalty and duty to provide all information requested by the consumer as a result of the rules listed in Articles 46, 52, I to V, and 54, § 3, of the Consumer Protection Code, as well as the principle of good- faith described in articles 4 and 51, IV, of the same law. Rule and principle are complementary therein, but day-to-day reality of the elderly and illiterate shows that the effectiveness of these rules is greatly compromised. Lack of complete information to the elderly and illiterate consumer compromises the free exercise of their expression of will, since it is not backed by the essential elements laid down by the contract. The focus of this work lies in the fact of asserting the necessity of the applicant or consignor to understand the clauses that he/she will be subject to. In other words, there is a need for an element that qualifies at will, making it a conscious one. This may be accomplished through the aid of a body constitutionally devised to defend the rights, with inalienable social and individual relevance. The Public Ministry, an entity constitutionally created to defend fundamental rights, has the duty to promote preventive measures to safeguard the interests of elderly and illiterate consumers. Prevent the occurrence of disputes and ensure the elderly and illiterate that his/her will is free is responsibility to be undertaken by the Public Ministry. This function of preventing conflicts and preserving the will of elderly and illiterate consumers can be widely exercised by signing terms of adjustment of conduct by Public Ministry and the banks, but also thorough information given to the elderly and illiterate consumers by the parquet member, about the content of the contract